AN ANALYSIS OF TRANSLATION TECHNIQUES USED IN “THE LITTLE PRINCE” MOVIE’S INDONESIAN SUBTITLE TEXT - Ramadhan, Jimmy; M. Syarfi, M. Syarfi; Masyhur, Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Translation in non-English speaking countries is important for communication between people with different cultures and languages. To acquire an accurate, clear and natural translation, a translator needs a what is called translation techniques which were proposed by Molina and Albir in 2002. It is a basis in a translation process, which is transferring a written text from the source language to target language. It is in fact the bottom line in this research is entitled „An Analysis of Translation Techniques Used in “The Little Prince” Movie‟s Indonesian Subtitle Text‟. In order to describe it, the writer used the descriptive qualitative approach. Besides, the writer also used the quantitative approach to compile the findings and presenting it in a table with the percentage of each technique‟s frequency. This research finds out there are 16 out of 18 techniques used in this subtitle and the most prominent technique used was the literal translation technique with a frequency of 299, or 28.23% of total data. While the least one was particularization technique which only occurred for 5 times (0.47% of total percentage). The writer also finds out that two of those techniques were not applied by the translator. These are on the ground that the writer could not identify any essential specifications of both techniques. They are description and variation technique.Key Words: Translation, Translation Techniques, Movie, Subtitle.